2016
DOI: 10.1007/s00068-016-0646-9
|View full text |Cite
|
Sign up to set email alerts
|

Severe intimate partner violence affecting both young and elderly patients of both sexes

Abstract: IPV leads to severe injury across all age groups among both male and female patients. The injury mechanism should be clearly defined for all trauma patients, keeping IPV in mind as a potential cause despite patient age or gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 21 publications
2
17
0
1
Order By: Relevance
“…Our results expand previous studies. IPV-inflicted injuries in our research were multiple, mainly located on the head, face, neck and upper limbs, as in previous research results [4,8,12,16,17]. Women with IPV-related injuries usually rank low on a severity index and less than 10% had serious lesions [17]; our results confirm the low severity of injuries.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results expand previous studies. IPV-inflicted injuries in our research were multiple, mainly located on the head, face, neck and upper limbs, as in previous research results [4,8,12,16,17]. Women with IPV-related injuries usually rank low on a severity index and less than 10% had serious lesions [17]; our results confirm the low severity of injuries.…”
Section: Discussionsupporting
confidence: 90%
“…Women subjected to IPV have been shown to experience repeated violent episodes [12] and use the Emergency Department (ED) more frequently, compared to women subjected to non-partner violence [1315]. Recent results from a sample study of ED visits in New York and from a self-report study in Helsinki revealed that patients visiting the ED as a result of IPV usually had multiple injuries [11,16]. The most common types of IPV-inflicted injuries were superficial injuries and contusions, wounds, sprains and strains.…”
Section: Introductionmentioning
confidence: 99%
“…Although both sexes are involved in IPV and experience IPV-related health outcomes, 31,32 researchers have traditionally focused on physical and nonphysical forms of violence perpetrated by a male partner against a female victim. 1,33 In the general population, lifetime prevalence of IPV against women has been estimated at 22%, 3,[34][35][36] with physical violence affecting 17%-34% and nonphysical violence affecting 12%-35% of women.…”
mentioning
confidence: 99%
“…The occurrence of limb injuries in the presentation of IPV differs in the literature with some studies indicating that limb injuries are not common [38] while others confirm the presence of limb injuries [39,40]. The deceased in our case study had upper and lower limb fractures including a possible defense (parry) type of fracture of the right forearm [3].…”
Section: Discussionmentioning
confidence: 84%